Památky Těšínského knížectví - Mezihoráková, Klára (Artefactum, 2016)
The publication consists of a series of essays devoted to the artistic heritage of the region of the former Duchy of Teschen, which existed as an independent unit from the late 13th century until 1920, when it was divided up between Czechoslovakia and Poland. The texts, written by various Czech and Polish authors, deal with selected heritage features and artists connected with this territory, disregarding the borders that were later drawn and thus recalling the former integral nature of the region and its art-historical riches and specific elements. The authors focus on various features of the artistic heritage, including examples of architecture, sculpture, and painting, over a timespan ranging from the Middle Ages to the 20th century. The publication also includes articles on themes that are particularly characteristic of the Teschen region – wooden sacred architecture and late-19th- and early-20th-century Protestant churches. The book contains texts written in Czech and Polish with English summaries. The authors of the articles are: Irena Adamczyk, Teresa Dudek Bujarek, Przemysław A. Czernek, Ondřej Haničák, Michaela Hrčková, Ludmila Hůrková, Marek Kwaśny, Andrzej Kozieł, Žaneta Lechovičová, Klára Mezihoráková, Hana Myslivečková, Zdeněk R. Nešpor, David Pindur, Dalibor Prix, and Romana Rosová.